Development of A Web-Based Recitation Program with Multiple Representations on Kinematics Material - Alfiana Dewi Febryanti; Muhammad Reyza Arief Taqwa (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2021)
This research aims to develop a web-based recitation program with multiple representations of kinematics material and to determine the feasibility of the product being developed. The recitation program aims to make it easier for students to deepen kinematics material outside lecture hours. This study uses the Research and Development (R&D) method with a 4D model development design consisting of 4 stages, namely defining, designing, developing, and disseminating. The data obtained from this research are quantitative data obtained from questionnaire assessment scores on the validation sheet and practicality test sheets based on the Likert scale, as well as qualitative data obtained from suggestions/comments from validators and students. The validity test was carried out by 1 physics lecturer at the State University of Malang and 2 physics lecturers outside UM, while the practicality test was carried out on 60 UM physics students who had obtained kinematics material. The data analysis technique used is the descriptive qualitative analysis and descriptive statistical analysis. In this research, the results of the data analysis of the program display validation were 87.67% and the results of the content validation data analysis were 93.31% with the valid category. While the practicality test obtained a percentage of 84.33% with practical criteria. The validation results and practicality test results show that the products developed are valid and suitable for use by students as independent teaching materials.